Isoflavonoids in non-leguminous taxa: a rarity or a rule? - Lapcík, Oldrich (Phytochemistry, 2007)
Isoflavonoids are characteristic metabolites in legumes and an overwhelming number of reports concerning them come from the Leguminosae. Nevertheless, the spectrum of isoflavonoid producing taxa includes the representatives of four classes of multicellular plants, namely the Bryopsida, the Pinopsida, the Magnoliopsida and the Liliopsida. At least 59 non-leguminous families have been reported to produce isoflavones sensu lato; coumestans have been reported in 3 families, coumaronochromones in 3, pterocarpans in 9 and rotenoids in 8 families. Prenylated isoflavones have been found in 15 non-leguminous families and isoflavone dimers, heterodimers or oligomers in three families. More than two hundred different isoflavonoid aglycones have been reported in non-legumes altogether. The number of individual structures is even greater if the variety of glycosides are considered. Enzymology and genetics of isoflavonoid biosynthesis have been studied almost exclusively in legumes, with the exception of a few model plants (i.e. Beta vulgaris, Arabidopsis thaliana, Nicotiana tabacum and Zea mays). The key step at the very beginning of the isoflavonoid metabolic pathway is the oxidation of flavanone connected with the migration of aryl moiety from C2 to C3 mediated by a CYP450 enzyme isoflavone synthase (IFS), which has been identified and cloned in multiple legumes and in sugar beet (Beta vulgaris, Chenopodiaceae). No information is available about the enzyme(s) responsible for the biosynthesis of isoflavonoid core in other taxa. Experimental data demonstrates the capability of numerous enzymes of non-legume origin to metabolize isoflavones as alternative substrates to other phenolics.
Keywords: Plant Proteins; Enzymes; Isoflavones; Humans; Fabaceae; lidé; rostlinné proteiny; isoflavony; enzymy